Osseointegration: Antibacterial Mesoporous Titania Films with Embedded Gentamicin and Surface Modified with Bone Morphogenetic Protein 2 to Promote Osseointegration in Bone Implants (Adv. Mater. Interfaces 9/2019). Issue 9 (9th May 2019) - Escobar, Ane; Muzzio, Nicolás; Coy, Emerson; Liu, Hui; Bindini, Elisa; Andreozzi, Patrizia; Wang, Guocheng; Angelomé, Paula; Delcea, Mihaela; Grzelczak, Marek; Moya, Sergio E.
Abstract : Mesoporous Titania Films (MTFs) are synthesized through the sol‐gel technique for gentamicin loading and delivery, and the functionalization of the MTFs surface with human recombinant bone morphogenetic protein 2. This doubly functionalized MTFs have been shown to be effective against S. aureus colonization and the presence of hrBMP‐2 enhances MC3T3‐E1 pre‐osteoblast cell attachment, proliferation and differentiation. More details can be found in article number1801648 by Ane Escobar, Sergio E. Moya, and co‐workers.